On some Himalayan species of the genus Mannerheimia Mäklin, 1880 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2024)
Taxonomic and faunistic data for four Himalayan species of the genus Mannerheimia Mäklin, 1880 are presented. Three species are redescribed and illustrated: M. cachemirica Coiffait, 1982 (India: Kashmir), M. emodensa Coiffait, 1977 (Nepal) and M. obscura Coiffait, 1982 (Pakistan, India, Nepal). A new synonymy is established: M. cachemirica = M. vicina Coiffait, 1982 syn. n. The habitus of M. scutellata Coiffait, 1982 (India: Kashmir) is illustrated. Mannerheimia obscura is recorded from Himachal Pradesh (India) and Nepal for the first time; a distributional map of this species is provided.